IbM PEMBENTUKAN POS EDUKASI AVIAN INFLUENZA UNTUK MENCIPTAKAN SISWA YANG TANGGAP AVIAN INFLUENZA DI PROVINSI BENGKULU - Heri Dwi Putranto; Hardi Prakoso; Nurmeliasari Nurmeliasari; Apri Andani Andani; Yossie Yumiati (Universitas Bengkulu, 2018)
Avian influenza (AI) has become a problem for livestock industry mainly for Indonesia poultry industry. It will cost for some economic values and activities, furthermore, it will also disturb the people’s daily lives for the probability of H5N1 virus transmission (from animal to human) which can be lead to deadly case in poultry and humans infected. By a collaboration with Dinas Kelautan, Peternakan dan Perikanan (DKPP), researchers have visited some schools including SMA Negeri 3 Pondok Kelapa, SMP N 2 Giri Mulya and SD Negeri 7 Kerkap. The purpose of this study was to establish school based educative shelter in order to improve student’s knowledge on AI issue. By a series of activities, extension on AI biosecurity activities followed by a practical demo on AI biosecurity and educative shelter establishment. Three (3) shelters were established in SMA Negeri 3 in District of Pondok Kelapa, SMP Negeri 2 in District of Giri Mulya and SD Negeri 7 in District of Kerkap. Keywords: Avian Influenza, Educative Shelter, IbM, Students Perceptive